1999
DOI: 10.1007/bf02357863
|View full text |Cite
|
Sign up to set email alerts
|

Integrated pest management of potato tuber moth in field and storage

Abstract: SummaryThe potato tuber moth (PTM), Phthorimaea opercalella (Zeller), is one of the most damaging pests of potatoes in field and storage. Tuber moth is active throughout the year in North Africa but is most active from late April to early August. Many cultural practices that are used by farmers to improve the yield and quality of potato can also limit the development of the potato tuber moth and minimise damage to tubers. As the farmers gain more experience with both agronomic practices and chemical insecticid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 8 publications
0
30
0
5
Order By: Relevance
“…Newly hatched larvae of PTM bores into leaves, shoots and stems of plants, as well as root tubers, and this feeding behavior makes it difficult to control this pest (Hanafi 1999;Sporleder et al 2007). PTM is becoming a serious problem in Brazil, particularly in potato (Solanum tuberosum L.) and tobacco (Nicotiana tabacum L.) crops.…”
Section: Introductionmentioning
confidence: 99%
“…Newly hatched larvae of PTM bores into leaves, shoots and stems of plants, as well as root tubers, and this feeding behavior makes it difficult to control this pest (Hanafi 1999;Sporleder et al 2007). PTM is becoming a serious problem in Brazil, particularly in potato (Solanum tuberosum L.) and tobacco (Nicotiana tabacum L.) crops.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated increasing susceptibility to nucleopolyhedrosis virus by additives such as fluorescent brighteners, GV-enhancing protein, and neem extract against lepidopteran hosts at low doses of each agent , 1999. Results from studies testing neem-based agents against insect pests vary depending on several factors, including neem preparation, concentration of azadirachtin, and insect species and age.…”
Section: Discussionmentioning
confidence: 99%
“…The potato tuberworm, Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae), is an important economic pest of potato crops and stored potatoes, causing high yield losses in warm climates worldwide (Radcliffe 1982, Hanafi 1999. This pest, originating in South America, has spread to almost all potato-producing areas throughout the world (von Arx et al 1990, Rondon 2010.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In North Africa, the rapid increase in population of P. operculella in the field prior to harvest results in heavy infestation during storage von Arx et al 1988;BenSalah and Aalbu 1992;Salah et al 1994;Laarif et al 2003). Tubers stored for seed can be treated with pyrethroids and organophosphates in certain cases (Islam et al 1990;Das et al 1992;Hossain et al 1994;Hanafi 1999;Keasar et al 2005), although the practice can be illegal and life threatening when used inappropriately. Under rustic storage conditions in the Philippines, granulo-viruses (GV) at 5 kg • ton -1 of tubers has been effective for up to 2 months of storage; treatment combinations of GV + Bt + deltametrhin + Lantana or deltamehtrin + Bt + GV yielded zero to low pest infestation; Bt alone was ineffective (Das et al 1992).…”
Section: Infestation In Storagementioning
confidence: 99%